Organización contable en la empresa master ferretería periodo octubre- diciembre 2021 - Chinchay Esmeraldas, Irene Valeria (2022)
The Curricular Integration Work named ACCOUNTING ORGANIZATION IN THE “MASTER FERRETERIA”, PERIOD OCTOBER- DECEMBER 2021 is oriented to organize and propose accounting tools, in such a way that facilitates the owner the generation of accounting information and so to know the real economic and financial situation of the company in order to make decisions to improve the performance of it. To fulfil with the first objective of the curricular integration work, it was necessary to begin the began the accounting process with the design of a plan and accounting manual according to the company needs, with its description and respective coding that facilitates the record of the operations, the lifting of the initial inventory through the physical goods verification, values and obligations that the company owns with an asset value of 2.339.480,10 its liabilities of 122.066,52 and equity of 2.217.413,58, the elaboration of the initial situation statement, detailing the assets, liabilities and equity accounts; diary book recording transactions in chronological order, general ledger, trial balance, work sheet until to get the financial statements, such as the income statement, the financial situation statement, and cash flow statement, reflecting reliable information and truthful of the economic and financial situation of the hardware store. To develop the multiple account system or periodic inventory was used with the purpose to record and control the movement of the company inventory; since it is a accounting record of easy application; allowing to get detail information in each one of the accounts that are in the system, thus at the end of the accounting period, it lets know if there is a gross profit or loss on sales. Finally, main registers and auxiliary formats were designed such as: auxiliary of purchases, sales consumption, depreciation and payment roles and provisions, where the financial and economic information of the entity have been detailed and consolidated; facilitating and simplifying record of the transactions that are carried out daily in the hardware store. Given the conclusion of the accounting process and the issuance of the respective financial statements, the company Master Ferreteria presents during the accounting period in the balance sheet a value of assets in 2.719.052,42 dollars, its liabilities in 369.064,41 dollars and a heritage of 2.349.988,01 dollars; and the income statement obtaining as results a net profit of 132.574,43 dollars, so that the Master Ferreteria is shown as a solid and competitive company within the sector in which it operates, obtaining a great profitability due to the increase in its sales, being significant information for its owner and based on it, makes decisions to the continued economic growth of his business.